2023
DOI: 10.1186/s13048-023-01122-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin resistance and abnormal menstrual cycle in Chinese patients with polycystic ovary syndrome

Abstract: Background Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disorder, which is characterized by insulin resistance (IR) and menstrual cycle disorders. IR is thought of as a pivotal cause of PCOS and related comorbidities. However, the link between IR and abnormal menstrual cycles in PCOS should be further studied. In this study, we clarified the dose–response relationship between IR and abnormal menstrual cycles in patients with PCOS. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Obesity is the most common cause of insulin resistance and compensatory hyperinsulinemia, which are the primary pathological features of PCOS. Previous studies have demonstrated that insulin resistance plays a role in determining the degree of menstrual irregularity in patients with PCOS ( 22 , 23 ). However, in the current study, for PCOS patients with an average BMI of 40.91 kg/m 2 , no significant differences were observed in HOMA-IR and AUC insulin of OGTT values among the different BMI groups; therefore, it is reasonable for these patients to have a similar response to SG in the remission of irregular menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is the most common cause of insulin resistance and compensatory hyperinsulinemia, which are the primary pathological features of PCOS. Previous studies have demonstrated that insulin resistance plays a role in determining the degree of menstrual irregularity in patients with PCOS ( 22 , 23 ). However, in the current study, for PCOS patients with an average BMI of 40.91 kg/m 2 , no significant differences were observed in HOMA-IR and AUC insulin of OGTT values among the different BMI groups; therefore, it is reasonable for these patients to have a similar response to SG in the remission of irregular menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine structural abnormalities like fibroids, polyps, and hyperplasia often underly metrorrhagia in premenopausal women. Endometrial cancer, though rare before menopause, has a peak incidence at 55-64 years old and should be ruled out in postmenopausal bleeding [8][9][10][11].…”
Section: Epidemiologymentioning
confidence: 99%